Analisis Tata Kelola Sistem Informasi Menggunakan Framework Cobit 2019 Pada Dukcapil Kota Salatiga - Handyan, Nelson Christopher; Rudianto, Christ (LPPM STIKOM Tunas Bangsa, 2024)
Information technology is an important and fundamental asset in a company or organization because the presence of good information technology will certainly support work effectiveness and maximum utilization of resources. One of the government organizations operating in the field of Community Services, namely DUKCAPIL, utilizes information technology as support in its operational processes. The problem faced by DUKCAPIL is that information system governance is not running well, especially in conveying information. Therefore, research was conducted on DUKCAPIL information system governance using the COBIT (Control Objective for Information and related Technology) framework, which is an IT governance framework that defines ways and methods for an organization. The research results show that the average level of capability achieved is at the Assisted Process level. This means each sub domain has been well defined and standardized. Even though almost all processes meet the requirements, there are still weaknesses in the implementation of processes that can be maximized to achieve adequate results. DUKCAPIL still needs to carry out the level 5 process, namely Optimizing Process, by providing regular training to human resources (HR) on existing Information Systems. In addition, companies must meet user needs to achieve the desired targets.